Case Report: Complete remission in a neonate with high-risk neuroblastoma harboring MYCN amplification and 1p deletion: a case for aggressive early intervention, and literature review - Gabitova, N. Kh.; Cherezova, I. N.; Osipova, I. V.; Sadykova, D. I.; Nasr, Dalal; Gobarah, Ayman A.; Arafat, Ahmed (Frontiers in Pediatrics, 2026)
Neuroblastoma is the most prevalent extracranial solid tumor in infancy and early childhood, accounting for 8%–10% of all pediatric malignancies and contributing significantly to cancer-related mortality. Its clinical spectrum ranges from spontaneous regression to aggressive metastatic disease, often influenced by underlying genetic aberrations such as MYCN amplification and chromosomal deletions (1p, 11q, and 17q). We present a rare case of a full-term male neonate diagnosed with stage 4 neuroblastoma originating from the left adrenal gland, exhibiting both MYCN amplification and 1p deletion. The patient had extensive liver metastases and supradiaphragmatic lymphadenopathy at diagnosis. Multimodal treatment, including intensive chemotherapy per the NB2004 protocol, surgical resection, high-dose consolidation chemotherapy, and autologous hematopoietic stem cell transplantation (AHSCT), led to complete remission by 11 months of age. Despite severe post-transplant complications such as sepsis and enteropathy, the patient remained disease-free with normal developmental milestones at follow-up. To the best of our knowledge, this is the first reported case of neonatal neuroblastoma with concurrent MYCN amplification and 1p deletion achieving favorable outcome through comprehensive multimodal therapy. This case underscores the importance of early diagnosis, genetic profiling, and aggressive treatment in managing high-risk neuroblastoma in neonates.